2019
DOI: 10.3390/su11226518
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Environmental Responsibility and Firm Information Risk: Evidence from the Korean Market

Abstract: Despite the potential benefits of a firm’s corporate environmental commitment to its information environment, few empirical studies examine the relationship between corporate environmental responsibility (CER) and firm information risk in emerging markets. In such markets, better corporate transparency and less information asymmetry are becoming increasingly important owing to firms’ poor governance structures, the lack of protection for investors, the substantial participation of unsophisticated individual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For instance, Deng and Cheng (2019) [41] find that CER and stock market performance has a positive correlation. In addition, researchers found that CER contributes to lowering a firm's information risk [46], increases firm risk [47,48], enhances value of shareholders [49], and increases board diversity [50]. However, there also exists studies that ESG activities negatively affect firm performance [51].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For instance, Deng and Cheng (2019) [41] find that CER and stock market performance has a positive correlation. In addition, researchers found that CER contributes to lowering a firm's information risk [46], increases firm risk [47,48], enhances value of shareholders [49], and increases board diversity [50]. However, there also exists studies that ESG activities negatively affect firm performance [51].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The notion of CSR is gaining attention not only because it is an ethical practice but also because there is a growing body of studies demonstrating financial return for the companies. For example, using a companies' corporate environment responsibility score and financial data, a study has shown that a company's commitment to environmental responsibility influences economic growth (Choi et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choi et al [19] explore how business can contribute to sustainable development by reviewing socially responsible firms and the effect of their corporate environmental responsibility (CER) information on business. They found that environmental responsibility has importance for profitability by improving information transparency and increasing shareholder value.…”
Section: Form and Contents Of The Thematic Issuementioning
confidence: 99%